Transient numerical study of projectiles undergoing cavitating flows - Yeo, Jovan Rui (Nanyang Technological University, 2023)
Supercavitation is a phenomenon when a gas or vapor pocket fully encloses a body travelling through a liquid medium. There are substantial benefits to be reaped such as eliminating skin friction drag entirely. However, the effect of a projectile’s geometry on the behavior of the cavitation pocket is not well understood, and understanding the generation and decay of the pocket would be useful in further development of such projectiles.